(untitled) (Applied Biological Research, 2017)
Fruits of pear (Pyrus pyrifolia) cv. Nijisseiki are vulnerable to post-harvest losses as its maturity time in north India coincides with summer months. Hence, to improve the storage life, the fruits were given post-harvest dip of calcium nitrate @ 0, 2, 3 and 4% and gibberellic acid (GA3) @ 0, 20, 40 and 60 ppm for 5 min. Treated and untreated (control) fruits were packed in CFB boxes and stored at low temperature conditions (0-1oC and 90-95% R.H) for 70 days. Fruits were analyzed for various physicochemical changes on 0, 30, 50 and 70 days after storage. Both calcium nitrate and GA3 treatments were effective in minimizing the physiological loss in weight (PLW) and maintaining the fruit firmness, total soluble solids (TSS), titratable acidity, total sugars content, sensory quality and pectin methyl esterase (PME) activity as compared to control during storage period. After 70 days of storage, minimum PLW (4.81%) and highest fruit firmness (3.88 kgf), sensory quality (7.15), TSS (12.35%) total sugars (8.45%), and PME activity (1.31 ml of 0.02 N NaOH used) were recorded in 3% calcium nitrate treated fruits.